A population-based assessment of metastatic hepatoblastoma in Texas reveals ethnic disparities - Espinoza, Andres F.; Scheurer, Michael E.; Chambers, Tiffany M.; Vasudevan, Sanjeev A.; Lupo, Philip J. (Frontiers in Public Health, 2023)
Background: Hepatoblastoma (HB) is the most common primary liver cancer in children with emerging evidence that incidence is increasing globally. While overall survival for low risk hepatoblastoma is >90%, children with metastatic disease have worse survival. As identifying factors associated with high-risk disease is critical for improving outcomes for these children, a need for a further understanding of the epidemiology of hepatoblastoma is warranted. Therefore, we conducted a population-based epidemiologic study of hepatoblastoma in Texas, a large state characterized by ethnic and geographic diversity. Methods: Information on children diagnosed with hepatoblastoma at 0-19 years of age for the period of 1995-2018 was obtained from the Texas Cancer Registry (TCR). Multivariable Poisson regression was used to calculate adjusted incidence rate ratios (aIRRs) and 95% confidence intervals (CIs) for each variable of interest. Joinpoint regression analysis was used to determine the trend in incidence of hepatoblastoma, overall and by ethnicity. Results: Overall, 309 children diagnosed with hepatoblastoma in Texas for the period of 1995-2018. Joinpoint regression analysis showed no joinpoints in the overall or the ethnic-specific analyses. Over this period, the incidence increased at 4.59% annually; with the annual percent change higher among Latinos (5.12%) compared to non-Latinos (3.15%). Among these children, 57 (18%) had metastatic disease at diagnosis. Factors associated with hepatoblastoma included male sex (aIRR=1.5, 95% CI:1.2-1.8, p=0.002); infancy (aIRR=7.6, 95% CI:6.0-9.7, p<0.001); and Latino ethnicity (aIRR=1.3, 95% CI:1.0-1.7, p=0.04). Additionally, children living in rural areas were less likely to develop hepatoblastoma (aIRR=0.6, 95% CI:0.4-1.0, p=0.03). While residence on the Texas-Mexico border association with hepatoblastoma approached statistical significance (p=0.06) in unadjusted models, this finding did not remain significant after adjusting for Latino ethnicity. The two factors associated with being diagnosed with metastatic hepatoblastoma included Latino ethnicity (aIRR=2.1, 95% CI:1.1-3.8, p=0.02) and male sex (aIRR=2.4, 95% CI:1.3-4.3, p=0.003). Conclusions: In this large population-based study of hepatoblastoma, we found several factors associated with hepatoblastoma and metastatic disease. The reasons for a higher burden of hepatoblastoma and metastatic hepatoblastoma among Latino children is unclear but could be due to differences in geographic genetic ancestry, environmental exposures, or other unmeasured factors.